Non - Jewish jew and other essays - "Deutscher, Isaac, 1907-1967" (London, 1981)
In these essays Deutscher speaks of the emotional heritage of the European Jew with calmness and clear-sightedness; as a historian he writes without anger but with compassion; as a non-Jewish Jew he writes without religious belief, but with a generous breadth of understanding.
Keywords: "Deutscher, Isaac 1907-1967 biography ."